Bile acid formation in man: metabolism of 7α-hydroxy-4-cholesten-3-one in bile fistula patients - Russell F. Hanson; Peter D. Klein; Gale C. Williams (Journal of Lipid Research, 1973)
7α-Hydroxy-4-cholesten-3-one is thought to be an intermediate in human bile acid synthesis. This conclusion is based on in vivo experiments in animals and on in vitro studies in which homogenates of animal and human livers were used. To further establish that this compound is an intermediate in human bile acid synthesis, its metabolism was studied in subjects with complete bile fistulas. After administration of 3H-labeled 7α-hydroxy-4-cholesten-3-one by single intravenous injection, approximately 85% of the administered isotope was recovered in the bile during the first 12 hr. More than 96% of the radioactivity recovered in the bile was identified as either chenodeoxycholic acid or cholic acid, with only a trace amount of the radioactivity present as neutral sterols. This study gives support to the hypothesis that 7α-hydroxy-4-cholesten-3-one is a natural intermediate in human bile acid synthesis.